SOCIAL STRUCTURE, ACTOR RELATIONS, AND CHALLENGES IN THE DEVELOPMENT OF THE COCONUT COIR INDUSTRY IN INDRAGIRI HILIR REGENCY - Mustaqim, Mustaqim; Herlon, Meki; Rifa’i, Ahmad; Rosnita, Rosnita; Yulida, Roza; Muwardi, Didi; Ridho, Zulhamid (Agripreneur : Jurnal Pertanian Agribisnis, 2025)
This study investigated the social structure, actor relations, and challenges in the development of the coconut coir industry in Indragiri Hilir Regency, one of Indonesia’s largest coconut-producing regions. Despite abundant raw materials, the downstream coconut coir sector remains underdeveloped and characterized by structural inequalities. A qualitative descriptive approach was applied, utilizing in-depth interviews, participatory observations, and document analysis involving key actors, including farmers, collectors, small and medium enterprises (SMEs), and government institutions. The findings revealed a hierarchical social structure and pronounced power asymmetries within the production chain. Farmers occupy subordinate positions due to limited capital, technology, and market information, functioning as price takers with minimal access to added value. Large collectors dominate pricing, distribution, and access to markets, creating a local oligopsonistic structure. Patron–client relations further reinforce economic dependency, limiting farmers’ autonomy to engage with alternative markets. Additionally, institutional weaknesses, fragmented government policies, rudimentary processing technologies, and insufficient logistics infrastructure hinder the development of a more inclusive and competitive value chain. The study highlights that social, economic, and institutional factors jointly shape structural barriers, underscoring the need for coordinated interventions to strengthen farmer agency, institutional capacity, and equitable value distribution.